The Nitrate Assimilatory Pathway in Sinorhizobium meliloti: Contribution to NO Production - Ruiz, Bryan; Le Scornet, Alexandre; Sauviac, Laurent; Rémy, Antoine; Bruand, Claude; Meilhoc, Eliane (Frontiers in Microbiology, 2019)
The interaction between rhizobia and their legume host plants culminates in the formation of specialized root organs called nodules in which differentiated endosymbiotic bacteria (bacteroids) fix atmospheric nitrogen to the benefit of the plant. Interestingly, nitric oxide (NO) has been detected at various steps of the rhizobium-legume symbiosis where it has been shown to play multifaceted roles. It is recognized that both bacterial and plant partners of the Sinorhizobium meliloti-Medicago truncatula symbiosis are involved in NO synthesis in nodules. S. meliloti can also produce NO from nitrate when living as free cells in the soil. S. meliloti does not possess any NO synthase gene in its genome. Instead, the denitrification pathway is often described as the main driver of NO production with nitrate as substrate. This pathway includes the periplasmic nitrate reductase (Nap) which reduces nitrate into nitrite, and the nitrite reductase (Nir) which reduces nitrite into NO. However, additional genes encoding putative nitrate and nitrite reductases (called narB and nirB, respectively) have been identified in the S. meliloti genome. Here we examined the conditions where these genes are expressed, investigated their involvement in nitrate assimilation and NO synthesis in culture and their potential role in planta. We found that narB and nirB are expressed under aerobic conditions in absence of ammonium in the medium and most likely belong to the nitrate assimilatory pathway. Even though these genes are clearly expressed in the fixation zone of legume root nodule, they do not play a crucial role in symbiosis. Our results support the hypothesis that in S. meliloti, denitrification remains the main enzymatic way to produce NO while the assimilatory pathway involving NarB and NirB participates indirectly to NO synthesis by cooperating with the denitrification pathway.